Global transcriptional responses of pneumococcus to human blood components and cerebrospinal fluid - Pettersen, Jens Sivkær; Høg, Frida Fabricius; Nielsen, Flemming Damgaard; Møller-Jensen, Jakob; Jørgensen, Mikkel Girke (Frontiers in Microbiology, 2022)
Streptococcus pneumoniae (pneumococcus) is a leading cause of severe invasive infectious diseases such as sepsis and meningitis. Understanding how pneumococcus adapts and survive in the human bloodstream environment and cerebrospinal fluid (CSF) is important for development of future treatment strategies. This study investigates the global transcriptional response of pneumococcus to human blood components and CSF acquired from discarded and anonymized patient samples. Extensive transcriptional changes to human blood components were observed during early stages of interaction. Plasma-specific responses were primarily related to metabolic components and include strong downregulation of fatty acid biosynthesis genes, and upregulation of nucleotide biosynthesis genes. No transcriptional responses specific to the active plasma proteins (e.g., complement proteins) were observed during early stages of interaction as demonstrated by a differential expression analysis between plasma and heat-inactivated plasma. The red blood cell (RBC)-specific response was far more complex, and included activation of the competence system, differential expression of several two-component systems, phosphotransferase systems and transition metal transporter genes. Interestingly, most of the changes observed for CSF were also observed for plasma. One of the few CSF-specific responses, not observed for plasma, was a strong downregulation of the iron acquisition system piuBCDA. Intriguingly, this transcriptomic analysis also uncovers significant differential expression of more than 20 small non-coding RNAs, most of them in response to RBCs, including small RNAs from uncharacterized type I toxin-antitoxin systems. In summary, this transcriptomic study identifies key pneumococcal metabolic pathways and regulatory genes involved with adaptation to human blood and CSF. Future studies should uncover the potential involvement of these factors with virulence in-vivo.